1998
DOI: 10.1159/000029811
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic Treatment with Liarozole on Cutaneous Inflammation, Epidermal Proliferation and Differentiation in Extensive Plaque Psoriasis

Abstract: Liarozole is a novel inhibitor of the enzyme cytochrome P450 which has inhibitory effects on the 4-hydroxylation of retinoic acid. Previous studies have shown that liarozole is effective in the treatment of psoriasis. We performed an immunohistochemical study on the lesional skin from 7 patients with extensive plaque psoriasis, who were treated with systemic liarozole 75 mg BID for a period of at least 2 months. The effects of liarozole treatment on clinical and histological parameters were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…For example, there is a decrease in the CD 11b-positive cell population (neutrophils, monocytes, and macrophages) and a decrease in epidermal ICAM-1 expression. 125 The side effects of liarozole include those of hypervitaminosis A. 125 Recently, more potent inhibitors in this class have been identified, such as R 115866.…”
Section: Experimental Therapeutic Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is a decrease in the CD 11b-positive cell population (neutrophils, monocytes, and macrophages) and a decrease in epidermal ICAM-1 expression. 125 The side effects of liarozole include those of hypervitaminosis A. 125 Recently, more potent inhibitors in this class have been identified, such as R 115866.…”
Section: Experimental Therapeutic Classesmentioning
confidence: 99%
“…125 The side effects of liarozole include those of hypervitaminosis A. 125 Recently, more potent inhibitors in this class have been identified, such as R 115866. 126 It remains to be determined whether a topical CYP26 inhibitor will be effective in the treatment of psoriasis.…”
Section: Experimental Therapeutic Classesmentioning
confidence: 99%
“…The reproducibility and sensitivity using the MIB-1 antibody instead of the Ki-67 antibody is better, because of a reduction of non-specific cytoplasm staining. In addition, another indication of the reliability and usefulness of the Ki-67/MIB-1 antibodies as proliferation markers is their potential to reveal the reduction of Ki-67 expression following antipsoriatic treatments [12, 16, 19, 20, 21, 23, 24, 25, 26, 27]. However, the large interstudy variability makes the comparison of absolute counts difficult.…”
Section: Discussionmentioning
confidence: 99%
“…KET is a general inhibitor of P450 enzymes, of which some are necessary for the metabolism of steroid hormones including vitamin D compounds or for androgen biosynthesis. Consequently, it has been shown that imidazole-like compounds including liarozole that have been demonstrated to exert inhibitory effects on the 4-hydroxylation of retinoic acid (RA) and/or on the 1,25-dihydroxyvitamin D/24-hydroxylase are effective in the topical or systemic treatment of inflammatory skin diseases including psoriasis [16][17][18]. Liarozole is an imidazole-like compound that inhibits the RA 4-hydroxylasemediated breakdown of all-trans-RA, causing elevation of plasma and cutaneous levels of RA.…”
mentioning
confidence: 99%
“…Liarozole is an imidazole-like compound that inhibits the RA 4-hydroxylasemediated breakdown of all-trans-RA, causing elevation of plasma and cutaneous levels of RA. Thus liarozole acts as a retinoid-mimetic drug and consequently has been found to be effective in the treatment of retinoid-responsive conditions such as chronic plaque psoriasis and ichthyoses [16][17][18].…”
mentioning
confidence: 99%